The Imperishable Sacrifice on Ralph Henry Barbour & George Randolph Osborne’s Thicker than Water - Nurdin, Dewi Syifanaya Firdausy; Rosyadi, Machfianita Mirza Ayu; Putri, Alvina Salshabilla Linjani; Ramadhani, Riska Dewi; Wijaya, Kusuma; Pasopati, Rommel Utungga (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article underlines the perspective of sacrifice in a flash fiction of Ralph Henry Barbour & George Randolph Osborne entitled Thicker Than Water. Sacrifice is a gift for a better view of the future as it is in line with the short story that shows a sacrifice of a brother to his beloved sister who needs to be blood donated because her blood is thinner than ordinary blood. Through qualitative method in explorative approach, this paper points to the relation between Bataille’s theory and Barbour & Osborne’s short story. In analysis, Barbour & Osborn’s short story shows the sacrifice and sincerity of an older brother who had to donate a lot of blood and even hold the pain for the sake of his younger sister in order to save her from dying. In conclusion, sacrifice in this story is engaged with sincerity in which all goodness of one's self is given to the other.